Palliative Screening Tools to Identify Palliative Care Consultation at Tertiary Hospital - Rudi Putranto; Ratih Arianita Agung; Cosphiadi Irawan; Czeresna Heriawan Soejono; Hamzah Shatri (Acta Medica Indonesiana)
Background: The need of palliative care is increasing, but it is not all achievable. It is necessary to identify palliative patients in order to provide the proper care according to the needs of the patients. Cipto Mangunkusumo Hospital has been making the identification using a palliative-patient screening questionnaire, but no performance assessment has been carried out on the screening tool. This study aimed to evaluate the performance of the screening-tool questionnaire used on palliative-care patients at Cipto Mangunkusumo Hospital in order to assess the need of palliative-care consultation and to find out the optimal cut-off point of palliative care screening tools. Methods: The design of this study is cross-sectional and was conducted at Cipto Mangunkusumo National Central Public Hospital in July – October 2019. The sampling was collected by consecutive sampling. The reliability test was performed by the intraclass correlation coefficient (ICC). The internal consistency was measured by the Cronbach’s-Alpha coefficient. The criterion-validity test was run by an evaluation using the Pearson test. Results: There were 64 subjects collected, the largest age group was 51-70 years (50%). Cancer was the main disease found in most of the subjects (56 people / 87.5%). The most common comorbidity was kidney disease (11 people). The most common palliative score distribution was 6 (15 people). The average score was 7.51. The mortality rate at the hospital was 51.6%, 33 patients from a total of 64 patients. From the palliative score distribution curve, the AUC value was 0.687 with a 95% CI (0.557-0.818). The optimal cut-off point was 8. All patients were palliative according to expert opinion based on WHO criteria. Conclusion: The performance of this tool is sufficient to screen palliative patients in a terminal and complex condition, but requires improvements to screen for patients who need early palliative care. The optimal cut-off point to determine the limit of consultation on palliative patients is found at score 8.